COPING STRATEGIES FOR FLOODS IN ANOMALOUS AREAS: A MISMATCH BETWEEN POTENTIAL ANALYSIS AND ACTUAL CONDITIONS IN THE KEMANG SUB-WATERSHED - Feby, ayu; Pramono, Retno Dwi (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
Flood disaster risk is one of the major issues faced by many cities and is expected to intensify with ongoing urban climate change (World Bank, 2023; IPCC, 2014). Jakarta is among the cities experiencing such challenges. In Jakarta’s elite Kemang area, there is virtually no buffer between the river and residential zones. This is further exacerbated by the river's shrinkage—leaving only 20% of its original width—aggravating flood conditions. Poor land use management that deviates from spatial planning has led to land-use conversion, construction in water catchment areas, and increased population density. Coping strategies are essential in responding to this situation. This study reveals that communities living along the riverbanks do not remain passive in the face of flood risks. It identifies anomalous areas that demonstrate a discrepancy between flood potential analysis and actual flood occurrences. Within these anomalous areas, various typologies of coping strategies used by the communities to deal with flooding can be identified.